Long-term outcomes of adolescents with juvenile-onset fibromyalgia into adulthood and impact of depressive symptoms on functioning over time. Issue 2 (February 2019) - Kashikar-Zuck, Susmita; Cunningham, Natoshia; Peugh, James; Black, William R.; Nelson, Sarah; Lynch-Jordan, Anne M.; Pfeiffer, Megan; Tran, Susan T.; Ting, Tracy V.; Arnold, Lesley M.; Carle, Adam; Noll, Jennie; et al.
Abstract : Abstract: Juvenile-onset fibromyalgia (JFM) is typically diagnosed in adolescence and characterized by widespread pain and marked functional impairment. The long-term impact of JFM into adulthood is poorly understood. The objectives of this study were to describe physical and psychosocial outcomes of youth diagnosed with JFM in early adulthood (∼8-year follow-up), examine longitudinal trajectories of pain and depressive symptoms from adolescence to young adulthood, and examine the impact of pain and depressive symptoms on physical functioning over time. Participants were 97 youth with JFM enrolled in a prospective longitudinal study in which pain symptoms, and physical and psychosocial functioning were assessed at 4 time points over approximately 8 years. At the time 4 follow-up (Mage = 24.2 years), the majority continued to suffer from pain and impairment in physical, social, and psychological domains. However, trajectories of pain and emotional symptoms showed varying patterns. Longitudinal analysis using growth mixture modeling revealed 2 pain trajectories (Steady Improvement and Rapid Rebounding Improvement), whereas depressive symptoms followed 3 distinct trajectories (Low-Stable, Improving, and Worsening). Membership in the Worsening Depressive symptoms group was associated with poorer physical functioning over time ( P < 0.001) compared with the Low-Stable and Improving groups. This study offers evidence that although JFM symptoms persist for most individuals, pain severity tends to decrease over time. However, depressive symptoms follow distinct trajectories that indicate subgroups of JFM. In particular, JFM patients with worsening depressive symptoms showed decreasing physical functioning and may require more intensive and consistent intervention to prevent long-term disability. Abstract : Longitudinal trajectory analyses showed decreasing pain over time in juvenile-onset fibromyalgia. A worsening depressive symptom trajectory was associated with the poorest outcomes in adulthood.